The effect of training program with repetition way to develop explosive power for legs and some basic skills for soccer players - Walid, mayad; Mahmoud, Munir (Journal of Physical Education, 2010)
The aim of the research was to detect the effect of the training program to develop explosive power for legs through preparation of a training program with repetition way, and using these exercises will develop the explosive power of legs through vertical jump test, as well as the effect of these exercises to develop shooting skill by testing scoring accuracy, the sample was selected in the manner and make pre test on 20-player from Technological University soccer team, academic year 2008/2009, and then divided the sample into two groups: control group and experimental group, matchmaking and underwent the experimental group to a training program, which designed by the researchers, consisting power exercises by using free weights and jump exercises, the player should exerted optimum ability and through the tests we will determine the training load for each player and each exercise. By using appropriate statistical tools to address the data that was recorded by the researchers to form the information in away to obtain the statistical results, which indicate the level of development of force explosive of the legs, through the application of the experimental method and the results of the study has appeared there is a significant difference in vertical jump test and shooting scoring accuracy, in favor of experimental group, throw the result of using training program which developed by researchers, the researchers concluded that the reason for this significant difference favoring the experimental group and the development of explosive power came through the implementation of exercises properly and taking into account individual differences of the players, and led to improved vertical jump and shooting scoring accuracy, and the researcher recommended further research in this area and different age groups should made, and to see the effect of training program inhalers in a scientific and thoughtful on other samples to match the level of the player and the quality of effectiveness to get the best results .